Estudo comparativo entre controladores PI e FGS-PI aplicados ao rastreamento da máxima potência em sistemas fotovoltaicos - Bigai, Mario Henrique (2025)
Climate change and the depletion of fossil resources are driving the transition to renewable energy sources, with solar photovoltaics playing an important role worldwide. In this context, tracking the maximum power point is essential to increase the system’s efficiency due to environmental conditions that impact the power generated by the photovoltaic modules. Tracking is done by controlling the DC-DC converter connected to the photovoltaic module. However, converters have non-linear dynamics, as does the photovoltaic module. Linearization is usually carried out at the maximum power point under standard test conditions, and the controller is designed for the linearization point. However, due to variations in environmental conditions, the system operates mainly outside the linearization point, which can compromise control and maximum power tracking performance. This work aims to design and compare PI and FGS-PI controllers applied to the maximum power tracking process under different environmental conditions in photovoltaic systems. Specifically, a battery charger using solar energy was studied, consisting of a Buck converter interfacing a photovoltaic panel and a battery. The proposed FGS-PI controller makes improving the system’s dynamic performance possible due to its adaptability to the system’s non-linearity by adjusting the controller’s gains. Genetic algorithm optimization was applied to the FGS system to adapt the PI controller gains more efficiently to optimize control performance without compromising system stability. The optimized FGS-PI controller outperformed the PI controller in terms of control performance, and when applied to maximum power point tracking, it showed improvements in tracking time. The results were observed both in the PSIM simulation environment and in practice.